Remarks at the Human Capital Conclave - Malpass, David (World Bank, Washington, DC, 2021)
David Malpass, President of the World Bank, discussed the importance of investing in human capital for a green, resilient, and inclusive recovery from the Coronavirus disease crisis. He highlighted three important measures: 1) investing in people; 2) efficient expenditures and good governance; and 3) freeing up fiscal space.